Pausing of RNA polymerase II disrupts DNA-specified nucleosome organization to enable precise gene regulation. - Gilchrist, D.A.; Dos Santos, G.; Fargo, D.C.; Xie, B.; Gao, Y.; Li, L.; Adelman, K. (Cell, 2010)
Metazoan transcription is controlled through either coordinated recruitment of transcription machinery to the gene promoter or regulated pausing of RNA polymerase II (Pol II) in early elongation. We report that a striking difference between genes that use these distinct regulatory strategies lies in the "default" chromatin architecture specified by their DNA sequences. Pol II pausing is prominent at highly regulated genes whose sequences inherently disfavor nucleosome formation within the gene but favor occlusion of the promoter by nucleosomes. In contrast, housekeeping genes that lack pronounced Pol II pausing show higher nucleosome occupancy downstream, but their promoters are deprived of nucleosomes regardless of polymerase binding. Our results indicate that a key role of paused Pol II is to compete with nucleosomes for occupancy of highly regulated promoters, thereby preventing the formation of repressive chromatin architecture to facilitate further or future gene activation.